Nutritional assessment of the area of influence of the marginal road. Biochemical studies, hemoglobin determinations, inorganic phosphorus and carotene - Guzmán Barrón, Alberto (1971)
The serum proteins are presented with constant figures in well-nourished and healthy subjects; hence their concentration is an index of nutritional status and results at the same time the quality and quantity of ingested food proteins because, before the deficiency this contribution a number of clinical processes that culminate mainly occur in growth arrest, and severe in the presence of Kwashiorkor in very young children cases.